AR PRODUCTION PHOTOGRAPHER MARKETING COMMUNICATION STRATEGY IN ATTRACTING CUSTOMER INTEREST - risa kartika lubis (SEAN Institute, 2022)
Marketing communication strategy is important in increasing the productivity of sales of a product and understanding of market conditions that can help business people to increase competition, one of which is by way of promotion. Communication, in terms of marketing, is not only used as a means or tool, but as an integral part of the company's marketing strategy or business people and even the company's mission in general. Just like other business actors, photographers also use marketing communication strategies to market the products and services they offer. It's just that there may be differences from other big business actors. One of the freelance photographers in Deli Serdang Regency which is quite developed, one of which is AR Production.